Epistemologi Anarkhis Paul Feyerabend dan Implikasinya terhadap Pemikiran Islam - Abdul Aziz Faradi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Nowadays, Islamic thought is trapped on the stagnancy of ideas. Such condition happens because the function of Islam changes, from an instrument for freedom to a rigid system of ideology. The similar pattern of change identified by Feyerabend also exists in the modern science. The similarity of the pattern inspired the writer to elaborate the concept of anarchy epistemology of Paul Feyerabend and its implication to the Islamic thought. This article uses philosophical hermeneutic approach by Gadamer in investigating meaningful sense of Feyerabend thought. The conclusion of the study ends up with the importance of returning Islamic thought to the pluralistic environment because Islam itself was not burn in a single thought but at least there are three epistemic patrons; Bayani, Burhani, and ‘Irfani.